MAKNA SIMBOLIK CATUS PATHA AGUNG SEBAGAI TEMPAT PELAKSANAAN YADNYA DI KABUPATEN BANGLI - I Wayan Wira; I Gusti Ngurah Sudiana; I Made Adi Brahman (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
The symbols in Hinduism are closely related and inseparable from the doctrine of the Divine (Hindu theology), because the symbols are expressions for bringing people closer to Him. They are arches or prefaces for the gods, the wheel of gods or the vehicle of the Gods, sacred buildings for the worshippers to worship Him. However, before we talk further, there is an idea that a city that was once a symbol of the kingdom now becomes the center of the district/city of the concept this is called Catus patha. Generally speaking, Catus Patha is the face of chess in which almost the entire Hindu community of Bali strongly believes that who sits on Catus pathha is Sanghyang Catur Bhuana, However, the catus patha that stands in the City of Bangli is a statue using the symbol Tri Murti. This research belongs to qualitative research with descriptive analysis with an experimental approach so that the researcher is the key instrument. Data collection techniques are triangulated, data analysis is inductive and the results of qualitative research emphasize meaning rather than generalization. The primary data source is from the results of field observations and in-depth interviews with the Sulinggih and Pinandita who are considered to know the research in this research. The informants are determined purposively sampling, that is to say, against those who really are in it. From the results of the analysis obtained Catus Patha the great in Bangli City is still an icon of government where there are still elements such as Puri (Istana), Wantilan (public open space), alun-alun (green open area), and Peken (market) despite some changes in the present day. As the center of the ceremony of the Yadnya, such as the tawur agung, ngerebeg, the naggluk merana, the ngulapin and other ceremonies, and in the sphere of society there is little controversy, among which are symbols less relevant to the other Catus Patha Agung. The statue of the Catus Patha Agung in the district of Bangli that the symbol is displayed in the symbol of the triumvirate, while according to some scribes and generally the Catus Patha Agung sthana Shang Hyang Chatur Bhuana is identified with the face or four-faced chess.